Peningkatan Soft Skill Mahasiswa Melalui Kegiatan Upgrading ‘Future Ready: Membangun Skill Untuk Dunia Nyata’ di Universitas Sunan Drajat Lamongan - Muhimmatul Hasanah; Biyati Ahwarumi; Chotibuddin; Muh Hasyim Rosyidi (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The Industrial Revolution 5.0 era requires students to possess not only academic abilities but also strong soft skills to adapt to social changes and the dynamic workforce. Students of Universitas Sunan Drajat (UNSUDA), as future leaders, need to develop interpersonal, communication, and character-building competencies to face global challenges. This community engagement activity aimed to enhance students’ soft skills through the Student Soft Skill Upgrading Program themed “Future Ready: Developing Skills for the Real World.” The implementation method adopted a participatory approach involving training sessions, interactive discussions, simulations, and reflective practices. The activity was conducted at the UNSUDA Graduate Hall, engaging approximately 100 students from various study programs. The results indicated an improvement in students’ self-awareness, communication effectiveness, and teamwork abilities. Participants also demonstrated greater confidence, empathy, and adaptability during collaborative activities. Overall, this program significantly contributed to shaping UNSUDA students into future-ready individuals with strong character and competitive qualities rooted in Islamic and professional values